Last-In First-Out Oligopoly Dynamics - Jaap H. Abbring; Jeffrey R. Campbell (Tinbergen Institute, 2006)
This paper extends the static analysis of oligopoly structure into an infinite-horizon setting with sunk costs and demand uncertainty. The observation that exit rates decline with firm age motivates the assumption of last-in first-out dynamics: An entrant expects to produce no longer than any incumbent. This selects an essentially unique Markov-perfect equilibrium. With mild restrictions on the demand shocks, a sequence of thresholds describes firms' equilibrium entry and survival decisions. Bresnahan and Reiss's (1993) empirical analysis of oligopolists' entry and exit assumes that such thresholds govern the evolution of the number of competitors. Our analysis provides an infinite-horizon game-theoretic foundation for that structure.
Keywords: L13; 330; Sunk costs; Demand uncertainty; Markov-Perfect equilibrium; LIFO; Oligopol; Sunk Costs; Markteintritt; Spieltheorie; Theorie